Land Administration and Management in Ulaanbaater, Mongolia - World Bank (Washington, DC, 2015)
The City of Ulaanbaatar (UB) is undergoing a historic transformation toward market-driven urban development. This growth remains strongly influenced by city policy decisions that affect the supply and location of land for public and private uses. Private investment is concentrated in well-serviced land located in the central portion of the city and along major transportation corridors, which represent a small part of the total built area of the city. Mongolian law allows UB residents free access to land for residential use, which is commendable because it can reduce a substantial portion of the overall cost of housing. Due to these land allocations, however, low-density urban expansion has occurred along the urban fringes, which imposes heavy costs on transportation and the provision of basic utilities for city residents and omits an important possible source of revenue for financing these improvements. The current city administration clearly recognizes that urban land represents one of the most important assets under its guardianship and management. In particular, the administration is making a systematic effort to proactively manage land in the public interest. Notable achievements include: (i) a nearly complete, current accounting inventory of city-owned capital assets; (ii) surveying, mapping, inventorying, and auditing public-use land; and (iii) decisive administrative measures to stop and correct past practices of nontransparent and sometimes unlawful land allocations to private sector actors, and to protect public land from informal occupation. However, such reforms are incomplete, and the city administration s efforts are constrained by existing national laws and regulations and conflicting perceptions about land as a designated public entitlement for residential use. There are several outstanding challenges the city faces in improving the administration of land and supporting the function of urban land and property markets to support investment and economic growth.